Sensory Brand Experience: Development and Validation in the Chinese Context - Gao, Fang; Lan, Xiaomin (Frontiers in Psychology, 2020)
Extant scales related to measuring the sensory aspect of a brand from the consumer’s perspective are typically either too abstract or too concrete. Thus, this study aimed to create a scale with a medium degree of abstraction by which to measure sensory brand experience. This entailed a process of scale development and validation. In study 1, we conducted a qualitative study to explore possible dimensions and items using semi-structured interviews. Several dimensions and items were proposed by combining findings from a literature review and the consumer interviews. In study 2, we examined the items and preliminarily tested the validity of the scale. The results show that, according to our scale, most of the brands considered could be differentiated in terms of the sensory experience they generate. The scale is thus deemed to have potential as a useful tool by which to evaluate the sensory quality of brands. In study 3, we further examined the items, verified the dimensions, tested the reliability and validity of the scale, and formally presented a final version of the scale. This final version comprises three dimensions and 10 items. The three dimensions represent, respectively, three important factors that may influence consumers’ perceptions and evaluations of the sensory quality of brands: the volume of sensory brand stimuli, the uniqueness of sensory brand stimuli, and the consistency between sensory brand stimuli and consumer. The scale’s reliability and validity are found to be satisfactory. Future research can thus employ the scale to assess the sensory experience of various brands, and even to rank brands accordingly. While the present study in the Chinese context is expected to provide valuable insights into the brand experience and sensory branding literature, further research could be conducted to validate the scale in other geographical and cultural contexts.